VarEPS: an evaluation and prewarning system of known and virtual variations of SARS-CoV-2 genomes. Issue Volume 50:Issue D1(2022) (11th October 2021) - Sun, Qinglan; Shu, Chang; Shi, Wenyu; Luo, Yingfeng; Fan, Guomei; Nie, Jingyi; Bi, Yuhai; Wang, Qihui; Qi, Jianxun; Lu, Jian; Zhou, Yuanchun; Shen, Zhihong; et al.
Abstract: The genomic variations of SARS-CoV-2 continue to emerge and spread worldwide. Some mutant strains show increased transmissibility and virulence, which may cause reduced protection provided by vaccines. Thus, it is necessary to continuously monitor and analyze the genomic variations of SARS-COV-2 genomes. We established an evaluation and prewarning system, SARS-CoV-2 variations evaluation and prewarning system (VarEPS), including known and virtual mutations of SARS-CoV-2 genomes to achieve rapid evaluation of the risks posed by mutant strains. From the perspective of genomics and structural biology, the database comprehensively analyzes the effects of known variations and virtual variations on physicochemical properties, translation efficiency, secondary structure, and binding capacity of ACE2 and neutralizing antibodies. An AI-based algorithm was used to verify the effectiveness of these genomics and structural biology characteristic quantities for risk prediction. This classifier could be further used to group viral strains by their transmissibility and affinity to neutralizing antibodies. This unique resource makes it possible to quickly evaluate the variation risks of key sites, and guide the research and development of vaccines and drugs. The database is freely accessible at www.nmdc.cn/ncovn .